Hematological shift in goat kids naturally devoid of prion protein - Reiten, Malin R.; Bakkebø, Maren K.; Brun-Hansen, Hege; Lewandowska-Sabat, Anna; Olsaker, Ingrid; Tranulis, Michael A.; Espenes, Arild; Boysen, Preben (Frontiers in Cell and Developmental Biology, 2015)
The physiological role of the cellular prion protein (PrPC) is incompletely understood. The expression of PrPC in hematopoietic stem cells and immune cells suggests a role in the development of these cells, and in PrPC knockout animals altered immune cell proliferation and phagocytic function have been observed. Recently, a spontaneous nonsense mutation at codon 32 in the PRNP gene in goats of the Norwegian Dairy breed was discovered, rendering homozygous animals devoid of PrPC. Here we report hematological and immunological analyses of homozygous goat kids lacking PrPC (PRNPTer/Ter) compared to heterozygous (PRNP+/Ter) and normal (PRNP+/+) kids. Levels of cell surface PrPC and PRNP mRNA in peripheral blood mononuclear cells (PBMCs) correlated well and were very low in PRNPTer/Ter, intermediate in PRNP+/Ter and high in PRNP+/+ kids. The PRNPTer/Ter animals had a shift in blood cell composition with an elevated number of red blood cells (RBCs) and a tendency towards a smaller mean RBC volume (P = 0.08) and an increased number of neutrophils (P = 0.068), all values within the reference ranges. Morphological investigations of blood smears and bone marrow imprints did not reveal irregularities. Studies of relative composition of PBMCs, phagocytic ability of monocytes and T-cell proliferation revealed no significant differences between the genotypes. Our data suggest that PrPC has a role in bone marrow physiology and warrant further studies of PrPC in erythroid and immune cell progenitors as well as differentiated effector cells also under stressful conditions. Altogether, this genetically unmanipulated PrPC-free animal model represents a unique opportunity to unveil the enigmatic physiology and function of PrPC.